(untitled) (Journal of Psychiatrists’ Association of Nepal, 2023)
Gender-based violence (GBV) is a public health concern with high rates of mental disorders. One Stop Crisis Management Centre (OCMC) was established in 2010 in different hospitals throughout the nation for the management of gender-based violence (GBV) against women by the Government of Nepal. With establishment of OCMC throughout the nation to tackle and manage these GBV, the role of mental health professionals has been highlighted in many ways. OCMC is full of opportunities and challenges to improve mental health issues of patients with GBV as well as define and recognize the roles and responsibilities of mental health experts.